Advances in Powder Metallurgy for High-Entropy Alloys - Sheetal Kumar Dewangan; CHEENEPALLI NAGARJUNA; 이한성; Rao K. Raja; Mohan Man; jain reliance; 안병민 (한국분말재료학회지, 2024)
High-entropy alloys (HEAs) represent a revolutionary class of materials characterized by their multi-principal element compositions and exceptional mechanical properties. Powder metallurgy, a versatile and cost-effective manufacturing process, offers significant advantages for the development of HEAs, including precise control over their composition, microstructure, and mechanical properties. This review explores innovative approaches integrating powder metallurgy techniques in the synthesis and optimization of HEAs. Key advances in powder production, sintering methods, and additive manufacturing are examined, highlighting their roles in improving the performance, advancement, and applicability of HEAs. The review also discusses the mechanical properties, potential industrial applications, and future trends in the field, providing a comprehensive overview of the current state and future prospects of HEA development using powder metallurgy.
Keywords: Powder metallurgy; High entropy alloys; Sintering